2022
DOI: 10.1186/s40814-022-01125-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of a motor coordination intervention on executive functions in kindergartners: a proof-of-concept randomized controlled trial

Abstract: Background Executive functions are pivotal for future academic and social functioning. Causal effects of physical activity on executive functions have been shown in adults. The primary objective of this study was to test the proof-of-concept (i.e., feasibility of implementation and acceptance) of a motor coordination intervention and a sedentary control condition in kindergartners and its preliminary effectiveness on subsequent executive function performance. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…The majority of the teachers consider an AB duration of more than 5min to be unrealistic (Chorlton et al, 2022). The unique contribution of this study is that the AB included only 5min dance activities (synchronized movements with the music), which was compared to a common type of aerobic AB used in previous studies (aerobic and strength activities) (Haas et al, 2022). According to the results of the study, the dance and aerobic groups showed a significant improvement in inhibition performance compared to pre-measurement.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The majority of the teachers consider an AB duration of more than 5min to be unrealistic (Chorlton et al, 2022). The unique contribution of this study is that the AB included only 5min dance activities (synchronized movements with the music), which was compared to a common type of aerobic AB used in previous studies (aerobic and strength activities) (Haas et al, 2022). According to the results of the study, the dance and aerobic groups showed a significant improvement in inhibition performance compared to pre-measurement.…”
Section: Discussionmentioning
confidence: 91%
“…However, the studies investigating the impact of a single session of exercise on cognitive functions have produced conflicting results. Some studies reported improvements in children's cognitive functions compared to the sedentary control group (Drollette et al, 2014;Ma et al, 2015;Schmidt et al, 2016), whereas other studies reported worsening effects (Egger et al, 2018;Gallotta et al, 2015), and others depicted no differences between AB and the sedentary control group (Calvert et al, 2019;Haas et al, 2022;Mavilidi et al, 2020;Yamazaki et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent randomized controlled trial conducted on preschoolers examined whether the MVPA intervention program positively affected EF skills, and these effects were found to have a significant correlation (Bai et al, 2022). However, there are inconsistencies in the articles suggesting that the MVPA is not significantly associated with EF in early childhood (Haas et al, 2022; McNeill et al, 2018; Willoughby et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…La hipótesis queda apoyada en distintos estudios (Hillman et al, 2014;Zach & Shalom, 2016) que obtienen mayores beneficios combinando el ejercicio físico que supone un mayor compromiso cognitivo (juegos motrices que requieren interacción y cooperación, y con estrategias de juego). Sin embargo, y aunque parece ser la variable de compromiso cognitivo una de las responsables de la obtención de mayores beneficios sobre el desarrollo de las FEs, pocos son los estudios que han investigado esta hipótesis en edades tempranas (Durán et al, 2015;Haas et al, 2022;Romero et al, 2018).…”
Section: Introductionunclassified